2017
DOI: 10.1242/bio.026211
|View full text |Cite
|
Sign up to set email alerts
|

Dlx3b/4b is required for early-born but not later-forming sensory hair cells during zebrafish inner ear development

Abstract: Morpholino-mediated knockdown has shown that the homeodomain transcription factors Dlx3b and Dlx4b are essential for proper induction of the otic-epibranchial progenitor domain (OEPD), as well as subsequent formation of sensory hair cells in the developing zebrafish inner ear. However, increasing use of reverse genetic approaches has revealed poor correlation between morpholino-induced and mutant phenotypes. Using CRISPR/Cas9-mediated mutagenesis, we generated a defined deletion eliminating the entire open rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 66 publications
(108 reference statements)
0
13
0
Order By: Relevance
“…Since the vestibular function in zebrafish larvae fundamentally relies on the normal development of the vestibular organ, knocking down the regulatory genes that control vestibular organ formation should lead to an abnormal vestibular function (Torres and Giráldez, 1998 ; Baker and Bronner-Fraser, 2001 ; Solomon and Fritz, 2002 ). Previous studies indicated that dlx3b and dlx4b have redundant function to regulate otolith formation in zebrafish; knocking down dlx3b , but not dlx4b , led to single-otolith formation in the ear while knocking down/knocking out both genes resulted in no-otolith/small ear vesicle phenotype (Solomon and Fritz, 2002 ; Liu et al, 2003 ; Schwarzer et al, 2017 ). Consistent with the previous studies (Mo et al, 2010 ; Cameron et al, 2013 ), the results of our dlx3b morphant larvae, which had only saccular otolith in their otic vesicles, suggest that utricular otolith is required for zebrafish LVOR.…”
Section: Discussionmentioning
confidence: 99%
“…Since the vestibular function in zebrafish larvae fundamentally relies on the normal development of the vestibular organ, knocking down the regulatory genes that control vestibular organ formation should lead to an abnormal vestibular function (Torres and Giráldez, 1998 ; Baker and Bronner-Fraser, 2001 ; Solomon and Fritz, 2002 ). Previous studies indicated that dlx3b and dlx4b have redundant function to regulate otolith formation in zebrafish; knocking down dlx3b , but not dlx4b , led to single-otolith formation in the ear while knocking down/knocking out both genes resulted in no-otolith/small ear vesicle phenotype (Solomon and Fritz, 2002 ; Liu et al, 2003 ; Schwarzer et al, 2017 ). Consistent with the previous studies (Mo et al, 2010 ; Cameron et al, 2013 ), the results of our dlx3b morphant larvae, which had only saccular otolith in their otic vesicles, suggest that utricular otolith is required for zebrafish LVOR.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, OEPD formation depends on Dlx3b and Dlx4b (Dlx3b/4b) in zebrafish and combined loss of foxi1 and dlx3b/4b eliminates all indications of otic specification ( Hans et al, 2004 ; Solomon and Fritz, 2002 ). At vesicle stages, absence of Dlx3b/4b causes a loss of early-born hair cells (also known as tether cells) and otoliths, large, solidified bio-crystals that mediate vestibular function ( Millimaki et al, 2007 ; Schwarzer et al, 2017 ). Since the loss of Dlx3 results in early embryonic lethality in mice, the role of Dlx3, which is dynamically expressed in the OEPD in amniotes, has not been addressed so far ( Brown et al, 2005 ; Chen et al, 2017 ; Morasso et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have established detection and analytical methods to measure the characteristic behavioral phenotypes, including locomotion, thigmotaxis, social behavior and aggressive behavior, in zebra sh [20,21]. The CRISPR/Cas9 technique is widely used for gene editing, and a number of transgenic zebra sh models have been developed [13,[22][23][24]. Notably, zebra sh models exhibit ASD-like phenotypes similar to those observed in human diseases.…”
Section: Introductionmentioning
confidence: 99%